Strategi Pengembangan Pasar Ekspor Bagi UMKM Melalui Pemanfaatan Teknologi Digital - Loqman Ananta Azaria; Sumainah Fauziah (Jurnal Pengabdian Kepada Masyarakat, 2023)
Technological developments are closely related to various types of trade systems in Indonesia, especially in export-import activities. This phenomenon is closely related to the use of technology in technology-based modern SMEs. The development of technology with various existing applications is the right choice because it makes international trade increasingly have a very broad market scope. The paradigm shift in international trade develops through the application of technology so that it is not outdated and looks boring. The export-import activities of an MSMEs require media that makes these MSMEs increasingly known by many people and is increasingly widespread with the development of digital technology